Association Between Acid-Sensing Ion Channel 3 Gene Variants and Balance Impairment in People With Mild Traumatic Brain Injury - Lee, Hsun-Hua; Ma, Hon-Ping; Ou, Ju-Chi; Ong, Jiann Ruey; Chen, Kai-Yun; Wu, Chung-Che; Chiu, Wen-Ta; Liao, Kuo-Hsing; Lin, Chien-Min; Lin, Shu-Yu; Wu, Dean; Huang, Yao-Hsien; et al. (Frontiers in Neurology, 2019)
Introduction: Dizziness and balance impairment are common symptoms of mild traumatic brain injury (mTBI). Acid-sensing ion channel 3 (ASIC3) is expressed in the vestibular and proprioceptive systems and associated with balance functions. However, whether the genetic variants of ASIC3 are associated with people who suffer dizziness and balance impairment after mTBI remained unknown. Materials and methods: A total of 200 people with mTBI and 109 non-mTBI controls were recruited. Dizziness, balance functions, and the ability to perform daily activities were assessed by Dizziness Handicap Inventory (DHI), and objective balance functions were investigated by the postural stability test. Three diseases-related genetic variants of ASIC3 were determined through polymerase chain reaction and followed by restriction fragment length polymorphism. The Student’s t-test and Mann-Whitney U test were used for normal and abnormal distributed data respectively. The regression was applied to adjust gender and age. The normality of continuous data was evaluated by Shapiro-Wilk test. Results: In the mTBI people, the rs2288645-A allele carriers exhibited a significantly worse physical domain DHI score (A-allele carriers: 11.39±8.42, non-A carriers: 8.76±7.87, p = 0.03). The rs4148855-GTC deletion carriers an exhibited significantly worse overall postural stability (GTC deletion carriers: 0.53±0.33, non-carriers: 0.46±0.20, p=0.03). In the controls, rs2288646-A allele carriers were significant worse in the medial-to-lateral postural stability (A-allele carriers: 0.31±0.17, non-A carriers: 0.21±0.10, p = 0.01) Conclusion: The present study demonstrated that ASIC3 genetic variants were associated with certain aspects of balance functions and dizziness questionnaires in people of mTBI and non-mTBI. It provides a possible evidence that ASIC3 could be a new target for the management of the balancing disorders. However, further investigations are warranted to elucidate the underlying mechanisms and clinical significance.